(3fThI GdTehd aj GdSaQ Edi GSdGeHhds - (3GdMSjfj GdBdhSj, CHh GdKfGA, TgGH GdOjf, eMehO Hf YHO Gddg Hf eMehO Hf OQhjT, J (B1270 (3g`s
(3ChdgG (B:s
(3SHMGf GdPj CSQi HYHOg abO CSQj Hj GdbVGA HYO aUdj ef fUH efUH GdEaJGA ef eOjfI GdSdGe Edi OGQ GdSdWfI GdYXei hYQL Hj GdbOQ GKQ eG YQL Ydi GdcOQ s
(3BNQgG (B:s
(3abSG djROLQhG hef jc MGReG adjbShG CMjGfG Ydi ef jQMe (B, (3dcf GdVQH gh BNQ VQhH GdYdGL hefgGL dG jSdc EdG EPG JYPQ cd efgGL agh cGdcj BNQ GdOhGA hcGdUYjO jSJYed EPG abO GdeGA Jes
(3NRGFfjI ePgHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\176s
(3EjVGM Gdecfhf (B2\648s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdLZQGajG hGdHdOGfs